2015
DOI: 10.2147/rrfu.s95901
|View full text |Cite
|
Sign up to set email alerts
|

MR-guided focused ultrasound for the treatment of adenomyosis: current insights

Abstract: Adenomyosis is a benign gynecological condition causing significant morbidity among women of reproductive age. The available treatments are currently limited in number and efficacy. While hysterectomy is curative, it is unacceptable to many women, particularly those wishing to conserve their fertility. Magnetic resonance-guided focused ultrasound surgery is a noninvasive treatment method that has been used to effectively treat uterine leiomyomata, but until recently has not been routinely used to treat adenomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
1
1
Order By: Relevance
“…However, one patient with adenomyosis in our study showed a lower shrinkage rate after 3 months than another study (our study vs. another study: 5.5% vs. 46.3%) [38]." should read as "No real-time monitoring in thermal damage in tissue was one of the limitations in ultrasonography-guided HIFU therapy [32], while it could be resolved under MR guidance. Besides, patients having pelvic endometriosis, adhesions locating between the uterus and bowel, or > 10-mm abdominal surgical scar are not recommended to receive HIFU therapy [33].…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…However, one patient with adenomyosis in our study showed a lower shrinkage rate after 3 months than another study (our study vs. another study: 5.5% vs. 46.3%) [38]." should read as "No real-time monitoring in thermal damage in tissue was one of the limitations in ultrasonography-guided HIFU therapy [32], while it could be resolved under MR guidance. Besides, patients having pelvic endometriosis, adhesions locating between the uterus and bowel, or > 10-mm abdominal surgical scar are not recommended to receive HIFU therapy [33].…”
contrasting
confidence: 54%
“…Keserci et al discovered that if the NPV achieved a ratio of at least 90%, the mean fibroid reduction ratio would be as high as 54 ± 13% [31]. A report of 80 patients with leiomyoma suggested that a larger NPV ratio would result in greater shrinkage and improved relief of symptoms [32]." should read as "A higher NPV ratio was found to be correlated with greater tumor volume shrinkage.…”
mentioning
confidence: 99%